Pitting Suppression of AISI 316 Stainless Steel Plates in Conditions of Ultrasonic Vibration - Georgii S. Vasyliev; Oleg M. Kuzmenko (International Journal of Chemical Engineering)
Plate heat exchangers are widespread type of equipment that suffers from pitting corrosion in chloride containing solutions. Anodic behaviour of AISI 316 stainless steel was tested in 3.5% NaCl solution in conditions of ultrasound vibration (27 kHz, 10 W). The potentiodynamic sweep, potentiostatic technique, and galvanostatic technique were used coupled with surface morphology investigation after polarization. The pitting potential increased from 0.26 ± 0.02 V/SSCE to 0.42 ± 0.05 V/SSCE, and repassivation potential increased from 0.03 ± 0.01 V/SSCE to 0.18 ± 0.04 V/SSCE when vibration was applied. The anodic current at applied potential in pitting region was two orders of magnitude lower in conditions of ultrasound vibration. A possible mechanism of vibration influence on pitting is proposed, which is the elimination of pit covers from the vibrating surface, vibration-induced electrolyte motion in and out of the pits, and repassivation of active metal inside the pits.